Strengthening Pancasila Student Profile through Innovative Learning at Madrasah Ibtidaiyah - Suyatno, Mangun; Rindaningsih, Ida (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The implementation of the independent curriculum in Indonesia aims to cultivate competencies aligned with national educational goals, particularly the Pancasila learner profile (P5). Specific Background: Despite the curriculum's introduction, there is limited research on its practical applications within Madrasah Ibtidaiyah, particularly regarding its alignment with local wisdom and sustainability themes. Knowledge Gap: Previous studies have not adequately explored the effectiveness of the independent curriculum in fostering Pancasila competencies among students. Aims: This study analyzes the independent curriculum as a vehicle for implementing the P5 project at MIN 2 Pasuruan, focusing on its processes and outcomes. Results: Employing a descriptive qualitative methodology, the research identifies that, although implementation is still developing, MIN 2 Pasuruan has effectively integrated local wisdom and sustainable practices into its curriculum. The findings demonstrate that project-based co-curricular activities contribute significantly to developing students' competencies and character in line with the Pancasila learner profile. Novelty: This research provides new insights into the application of the independent curriculum in Madrasah Ibtidaiyah settings, emphasizing local cultural relevance. Implications: The study underscores the importance of continued adaptation and enhancement of the independent curriculum to better support the holistic development of Pancasila learners, offering practical recommendations for educators and policymakers. Highlights: Integration of Local Wisdom: MIN 2 Pasuruan incorporates local cultural themes to enrich the independent curriculum. Project-Based Activities: Co-curricular projects are essential in developing competencies aligned with the Pancasila learner profile. Ongoing Development: While implementation is in progress, efforts to align with the independent curriculum show promise for future improvements. Keywords: Independent Curriculum, Pancasila learner profile, Madrasah Ibtidaiyah, local wisdom, project-based learning.